1991
DOI: 10.1177/153857449102500102
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Flow Enhancement by Impulse Compression

Abstract: Preliminary observations of rapid relief of ischemic rest pain following application of a foot impulse compression device prompted this study to quantify its immediate effects.Blood flow was calculated by means of a duplex ultrasound imager interfaced with a Doppler spectrum analyzer.Twelve normal subjects and 10 patients with peripheral vascular disease (mean Doppler ankle/brachial systolic pressure index = 0.62 (range 0.33-0.74) were studied. Mean resting blood flow ( SD) was not significantly different in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…Previous studies have determined that this timing and rate resulted in the maximal venous return in normal volunteers. 20 After a 10-minute baseline period, in which the popliteal artery blood flow was measured 5 times, IPFCC was applied for 10 minutes. During the IPFCC application, popliteal artery blood flow was measured an additional 5 times.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have determined that this timing and rate resulted in the maximal venous return in normal volunteers. 20 After a 10-minute baseline period, in which the popliteal artery blood flow was measured 5 times, IPFCC was applied for 10 minutes. During the IPFCC application, popliteal artery blood flow was measured an additional 5 times.…”
Section: Methodsmentioning
confidence: 99%
“…Using xenon 133 clearance rates, Gaskell and Parrott 24 demonstrated that pneumatic foot and ankle compression increased the blood flow 80% in the limbs of sitting patients with peripheral arterial disease. More recently, Morgan and associates 20 showed that foot compression not only increased venous return but also produced a postcompression arterial hyperemia. Similar results were found in another study in which calf compression was applied.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…[282][283][284][285][286][287][288] Women constituted 30% of participants in the studies of lower extremity pneumatic compression as treatment for symptomatic PAD that evaluated clinical outcomes and reported gender. 289 -291 These studies each included Յ50 patients and did not report any gender-specific analyses.…”
Section: Lower Extremity Pneumatic Compressionmentioning
confidence: 99%
“…[37][38][39] The A-V Impulse System was developed to mimic the natural physiological processes which maintain blood flow and has been shown to improve venous return and arterial blood flow in the extremities. 40,41 The proposed mechanism of action is that intermittent pneumatic compression leads to improved emptying of the lower extremity veins and lowered venous pressure which in turn results in an increase in arterio-venous pressure gradient and an increase in lower extremity arterial blood flow. [42][43][44] In a cohort study of 40 lower limbs of 30 subjects, the application of intermittent pneumatic compression to calf and foot greatly enhanced popliteal artery blood flow.…”
mentioning
confidence: 99%